2008
DOI: 10.1016/j.ejpb.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced skin penetration of P20 phosphopeptide using protein transduction domains

Abstract: Protein transduction domains (PTDs) were recently demonstrated to increase the penetration of the model peptide P20 when the PTD and P20 were covalently attached. Here, we evaluated whether non-covalently linked PTDs were capable of increasing the skin penetration of P20. Two different PTDs were studied: YARA and WLR. Porcine ear skin mounted in a Franz diffusion cell was used to assess the penetration of P20 in the stratum corneum (SC) and viable skin (VS); VS consists of dermis and epidermis without SC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 10 publications
4
30
0
Order By: Relevance
“…Previous studies have showed the effective transdermal skin delivery of proteins and peptides employing CPPs including Tat (Trans-activating transcriptional activator), YARA, WLR, and 9R peptides [26][27][28][29]. In the present study, we also showed that protein transduction method using 11R was valuable for the transdermal delivery of EGFP and HQ.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have showed the effective transdermal skin delivery of proteins and peptides employing CPPs including Tat (Trans-activating transcriptional activator), YARA, WLR, and 9R peptides [26][27][28][29]. In the present study, we also showed that protein transduction method using 11R was valuable for the transdermal delivery of EGFP and HQ.…”
Section: Discussionsupporting
confidence: 60%
“…This result was correlated to previous studies which showed that the interaction of the CPPs including Tat peptide with skin lipids may be the main transport across the SC, since this interaction may destabilize the SC resulting in an increase in the membrane permeability (Rothbard et al, 2000). Another suggested mechanism of transport was via the tight junctions which allowed penetration into the viable skin layers (Lopes et al, 2008). Kang et al (2010) studied the in vitro and in vivo skin penetration effect of Tat-coated elastic liposomes, they found that the Tat peptide could increase the flux of the liposomes by about 20%.…”
Section: Transdermal Absorption Through Rat Skinsupporting
confidence: 89%
“…This result is consistent with an earlier report that stated that the noncovalent WLR fragment, one of the penetrating peptides, was twice as effective in promoting the penetration of macromolecules into the skin. 19 It is also supported by an earlier report stating that several penetrating peptides are able to interact with lipids in the stratum corneum and enter into a layer of cells via a macropinocytosis mechanism, forming a gradient from the outer to the inner cell layers, thus facilitating the delivery of drug. 39 …”
Section: Kang Et Almentioning
confidence: 68%
“…Some experiments have demonstrated that cell-penetrating peptides including YARA, WLR, R9, and Tat (Trans-activating transcriptional activator) peptides were useful not only for intracellular delivery but also for promoting the skin penetration of molecules in mice. 19,20 A recent study showed that Tat peptide facilitates the translocation of drugs into immune cells in the skin. 21 Therefore, a novel Tat peptide-admixed EL (EL/T) containing HST was developed.…”
Section: Introductionmentioning
confidence: 99%